TEACHER’S STRATEGIES USED TO REDUCE SPEAKING ANXIETY IN ENGLISH CLASSROOM AT SMKN 1 KEDIRI - Hamida, Reka Hani; Riwayatiningsih, Rika; Suhartono, Suhartono (Media Inovasi Pendidikan dan Pembelajaran, 2024)
This research aims to identify and reduce speaking anxiety among students at SMKN 1 Kediri. The study uses a qualitative research design, employing interviews and observations to gather data from English teachers. The collected data will be analyzed using thematic analysis to identify recurring patterns and themes related to the strategies used by teachers. The study found that there are several ways to reduce anxiety, such as providing examples of speaking English in the classroom and assigning tasks that lead to speaking and writing in various instruments or textbooks. The relationship between emotions and anxiety in foreign language classes affects students' self-esteem and achievement in foreign language learning. The traditional